Employment status of patients with chronic inflammatory demyelinating polyradiculoneuropathy. Issue 3 (29th July 2018) - Bjelica, Bogdan; Basta, Ivana; Bozovic, Ivo; Kacar, Aleksandra; Nikolic, Ana; Dominovic‐Kovacevic, Aleksandra; Vukojevic, Zoran; Martic, Vesna; Stojanov, Aleksandar; Djordjevic, Gordana; Petrovic, Milutin; Stojanovic, Miroslav; et al.
Abstract : It has been previously shown that patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) who are unemployed or retired have worse quality of life. The aim of this study was to assess predictors of early retirement in CIDP. One hundred five patients with CIDP were included. Following measures were used: questionnaire on employment status, Medical Research Council Sum Score, INCAT disability score, Beck Depression Inventory, and Krupp's Fatigue Severity Scale. At the moment of testing, 2% of patients were students, 15% were employed, 9% were unemployed due to CIDP, 9% were unemployed but not due to CIDP, 28% were retired early due to disability caused by CIDP, and finally 37% were in old‐age pension. Mean age when patients retired due to CIDP was 50 ± 8 years. Mean time from CIDP onset to retirement was 2.7 ± 2.3 years. Older age at onset, lower education, and more severe weakness at the time of diagnosis were significant predictors of early retirement due to CIDP. Retired patients were 12 times more likely to suffer from depression, compared to employed patients (OR = 12.2, 95% CI = 1.41‐100, P  < 0.01), and eight times more likely to have fatigue (OR = 8.2, 95% CI = 1.89‐35.82, P  < 0.01). Older patients with lower education and more severe weakness at the time of diagnosis were most likely retired due to CIDP. Early retirement was associated with depression and fatigue. Therefore, maintaining employment should be an important aim in the management of CIDP patients.